The role of marketing audit in improving performance in economic units (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aimed to introduce marketing audit and the importance of its desired goals when applied in economic units. It highlighted the role of auditing marketing activities and processes in improving performance, in addition to analyzing and auditing the performance of the Mesopotamia General Seed Company (case study) to help identify deficiencies in marketing performance. To achieve the research objective, data was collected to draft the questionnaire based on previous studies related to marketing audit and black marketing, as well as the researcher's field experience at the Mesopotamia General Seed Company and its factories. The researcher distributed 80 questionnaires, retrieving 73 valid ones. The researcher visited the respondents at their workplaces, which required considerable time and effort, especially after adopting personal interviews with most respondents to clarify the questionnaire items. The research concluded that the analysis of results showed all standard deviations were very acceptable and within range, indicating reduced data dispersion. The t-test values for the questionnaire were very high with significance less than (0.001), indicating a statistically significant relationship at the level of (0.000) for the role of the four dimensions in the reality of applying marketing audit and improving performance at the company (case study). The research recommended the need to build an integrated system for collecting and analyzing marketing information, which aids in identifying market opportunities and risks, better directing strategies, and designing flexible marketing plans that can be adjusted according to market changes and customer needs, with regular audits adopted for them.